A Role of Cholesterol in Modulating the Binding of α-Synuclein to Synaptic-Like Vesicles - Man, Wing K.; De Simone, Alfonso; Barritt, Joseph D.; Vendruscolo, Michele; Dobson, Christopher M.; Fusco, Giuliana (Frontiers in Neuroscience, 2020)
α-Synuclein (αS) is a presynaptic protein whose aggregation is associated with Parkinson’s disease (PD). Although the physiological function of αS is still unclear, several lines of evidence indicate that this protein may play a role in the trafficking of synaptic vesicles (SVs) during neurotransmitter release, a task associated with its ability to bind SVs and promote their clustering. It is therefore crucial to identify the cellular factors that modulate this process. To address this question, using nuclear magnetic resonance (NMR) spectroscopy we have characterized the role of cholesterol, a major component of the membrane of SVs, in the binding of αS with synaptic-like vesicles. Our results indicate that cholesterol can act as a modulator of the overall affinity of αS for SVs by reducing the local affinity of the region spanning residues 65–97 in the non-amyloid-β component (NAC) of the protein. The increased population of bound states that expose the region 65–97 to the solvent was found to induce stronger vesicle-vesicle interactions by αS. These results provide evidence that cholesterol modulates the clustering of synaptic vesicles induced by (α)S, and supports the role of the disorder-to-order equilibrium of the NAC region in the modulation of the biological properties of the membrane-bound state of αS.